Atividades de aventura e educação ambiental como foco nos periódicos da área de Educação Física - Figueiredo, Juliana de Paula [UNESP]; Schwartz, Gisele Maria [UNESP] (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2013)
This qualitative study aimed at analyzing the articles that deal with different approaches and methodological strategies linking the themes of adventure activities and environmental education in journals of Physical Education area. An exploratory research was conducted in journals with A concept in 2011 WebQualis CAPES platform. The results show that this relationship is few explored in the area and the studies emphasize only some aspects, requiring therefore new approaches.

Este estudo, de natureza qualitativa, objetivou analisar os artigos que tratam sobre as diferentes abordagens e estratégias metodológicas relacionando as temáticas atividades de aventura e educação ambiental, em periódicos da área de Educação Física. A pesquisa exploratória foi realizada nos periódicos da área com estrato “A”, na avaliação WebQualis CAPES 2011. Os resultados evidenciam que esta relação é pouco explorada na área e os estudos privilegiam apenas alguns aspectos, necessitando, assim, novas reflexões.
Adventure activities and environmental education in Physical Education journals
Keywords: Physical Education; Adventure Activities; Environmental Education